PENGARUH LATIHAN DRILL SMASH FRONT AND BACK TERHADAP KEMAMPUAN SMASH OPEN PADA ATLET BOLA VOLI DI KLUB KAE NTT - Asmara, Anjas; Johan Irmansyah; Muhsan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aims to determine the effect of front and back smash drill training on the open smash ability of volleyball athletes at the KAE NTT Mataram club in 2023. This research uses a one-group pretest-posttest design. The population of the study consists of 20 volleyball athletes, all of whom were selected using total sampling. The data were collected using a volleyball smash ability test instrument (Nurhasan, 2001), and data analysis was performed using the t-test by comparing the mean scores from pretest and posttest results. The results show that the front smash drill significantly affects the open smash ability, with a t-count of 5.582 > t-table 1.833 at a significance level of 5%. Similarly, the back smash drill also shows significant effects with a t-count of 4.932 > t-table 1.833. The findings suggest that both training methods effectively improve the open smash ability of volleyball athletes. Additionally, there was no significant difference between the two training methods.. Keywords: drill smash front and back, smash open, volleyball, sport skills Penelitian ini bertujuan untuk mengetahui pengaruh latihan drill smash front dan back terhadap kemampuan smash open pada atlet bola voli di klub KAE NTT Mataram tahun 2023. Penelitian ini menggunakan desain one-group pretest-posttest. Populasi dalam penelitian ini terdiri dari 20 atlet bola voli yang dipilih menggunakan teknik total sampling. Data dikumpulkan menggunakan instrumen tes kemampuan smash bola voli (Nurhasan, 2001), dan analisis data dilakukan menggunakan uji t dengan membandingkan nilai rata-rata dari hasil pretest dan posttest. Hasil penelitian menunjukkan bahwa latihan drill smash front berpengaruh signifikan terhadap kemampuan smash open, dengan t-hitung 5.582 > t-tabel 1.833 pada taraf signifikansi 5%. Demikian juga, latihan drill smash back menunjukkan pengaruh signifikan dengan t-hitung 4.932 > t-tabel 1.833. Temuan ini menunjukkan bahwa kedua metode latihan efektif dalam meningkatkan kemampuan smash open pada atlet bola voli. Selain itu, tidak ada perbedaan signifikan antara kedua metode latihan tersebut.